An analytical model of label-free nanoscale chemical imaging reveals avenues toward improved spatial resolution and sensitivity - Yide Zhang; Ufuk Yilmaz; Gustavo Vinicius Bassi Lukasievicz; Liam O’Faolain; Bernhard Lendl; Georg Ramer (Proceedings of the National Academy of Sciences, 2025)
Atomic force microscopy–infrared spectroscopy (AFM-IR) is a photothermal scanning probe technique that combines nanoscale spatial resolution with the chemical analysis capability of mid-infrared spectroscopy. Using this hybrid technique, chemical identification down to the single molecule level has been demonstrated. However, the mechanism at the heart of AFM-IR, the transduction of local photothermal heating to cantilever deflection, is still not fully understood. Existing physical models only describe this process in few special cases but not in many of the types of sample geometries encountered in the practical use of AFM-IR. In this work, an analytical expression for modeling the temperature and photothermal expansion process is introduced, verified with finite element simulations, and validated with AFM-IR experiments. This method describes AFM-IR signal amplitudes in vertically and laterally heterogeneous samples and allows studying the effect of position and size of an absorber, pump laser repetition rate and pulse width on AFM-IR signal amplitudes and spatial resolution. The analytical model can be used to identify optimal AFM-IR experimental settings in conventional and advanced AFM-IR modes (e.g., tapping mode, surface-sensitive mode). The model also paves the way for signal inversion based superresolution AFM-IR.